Blocks of ice from ice jam beside log cabin, Fortymile, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: 2524 On verso of image: Ice jam at 40 Mile. Huge ice blocks driven up bank to cabins. Fortymile is located at the junction of Bullion Creek and North Fork Fortymile River, 37 miles southwest of Eagle, Yukon-Tanana Highway. It is a former telegraph station established in 1903 by the U.S. Army Signal Corps and originally called North Fork after the stream. The prospectors called it Fortymile. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number